Oromandibular reconstruction with double‐skin paddle fibular free flap: A systematic review and meta‐analysis. Issue 7 (6th July 2021) - Lucattelli, Elena; Brogi, Mattia; Cipriani, Federico; Innocenti, Marco; Cannamela, Giacomo; Innocenti, Alessandro
Abstract: Background: Reconstruction of complex head and neck defects is challenging, especially when more than one soft‐tissue subunit is involved. The osteocutaneous fibular flap underwent continual evolution to improve its soft‐tissue characteristics, such as including a second skin island. The purpose of this study was to evaluate outcomes regarding oromandibular reconstruction with a double‐skin paddle fibular free flap (DSPFFF) using three different techniques: central de‐epithelialized skin paddle, distally‐based double‐skin paddle (DSP), or proximally and distally‐based DSP. Methods: A systematic review was performed in December 2020 using Pubmed and MedLine Ovid databases according to the PRISMA guidelines. A meta‐analysis of functional outcome and complications was performed to estimate single incidence rates. Results: A total of 449 patients were included, with a follow‐up of 1–84 months, where 330 patients underwent reconstruction with the first technique, 23 patients with the second technique, and 96 patients with the third technique. The meta‐analysis showed an overall good functional outcome and a low‐complication rate for oromandibular reconstruction with DSPFFF. A better functional outcome and a lower complication rate were found when a distally‐based DSPFFF was harvested compared to a proximally and distally‐based DSPFFF. Conclusion: The DSPFFF was found to be useful and reliable for reconstructing composite and extensive head and neck defects, with an overall good functional outcome and a low‐complication rate. The meta‐analysis showed a better positive outcome on distally‐based DSPFFF rather than proximally and distally‐based DSPFFF. In addition, distally‐based DSPFFF showed a lower complications rate when compared with proximally and distally‐based DSPFFF.